Terrorism and (Other) Extremisms - Klampfer, Friderik (Analiza: časopis za kritično misel, 2025)
The article pursues two goals: to provide a working definition of terrorism and to critically evaluate the argumentative strategies leading to its near-universal moral condemnation. The author advocates for a definition of terrorism tailored to the needs of moral evaluation: the indiscriminate use of violence—or the serious threat thereof— with the aim or purpose of coercing (authorities) into implementing more or less radical political or social changes. Regarding the second, the author acknowledges that terrorists, through deliberate, but indiscriminate physical and psychological violence, assume a heavy moral burden. However, the argument is made that terrorism is not significantly different in this respect from other forms of politically motivated violence that are generally tolerated or even celebrated and admired, such as armed uprisings, and wars. Whether terrorism ultimately collapses under this moral burden will depend on the concrete justification, interpretation, and application of the principle of civilian immunity—a task far more challenging upon reflection than its commonly assumed. Finally, there are no compelling reasons to equate terrorism with extremism, especially when one considers how much more lenient we are toward other forms of politically motivated violence, which are, at best, morally equivalent to terrorism and, at worst, inferior.